PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESIBILITAS LAPORAN KEUANGAN DAERAH TERHADAP TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH KABUPATEN JEPARA - Aliyah, Siti; Nahar, Aida (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2012)
This research aims to empirically examine the effect of regional financial statement presentation andaccessibility of financial statements for transparency and accountability in financial management. Theresearch was conducted in Jepara district, for four months from January to April 2012. The samplingmethod used is proporsionate stratified random sampling; the sample is then determined by 40 members oflocal legislative council and 36 NGOs. For this research the data analyzed using multiple linear regressionwith tools statistical program, after test the classical assumptions are met. The results of this research showthat the presentation of the financial statements and the accessibility of the area of financial reportingpartial or jointly positive effect on transparency and accountability in financial management.Keywords:local financial reports, accessibility, transparency and accountability